2010
DOI: 10.1158/0008-5472.can-09-4224
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase Inhibitor Induces Accelerated Senescence in Irradiated Breast Cancer Cells and Tumors

Abstract: Persistent DNA double-strand breaks (DSB) may determine the antitumor effects of ionizing radiation (IR) by inducing apoptosis, necrosis, mitotic catastrophe, or permanent growth arrest. IR induces rapid modification of megabase chromatin domains surrounding DSBs via poly-ADP-ribosylation, phosphorylation, acetylation, and protein assembly. The dynamics of these IR-induced foci (IRIF) have been implicated in DNA damage signaling and DNA repair. As an IRIF reporter, we tracked the relocalization of green fluore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
114
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 22 publications
8
114
0
Order By: Relevance
“…While several studies have previously shown that epithelial cancer cells readily undergo senescence after radiation treatment in vitro (reviewed in ref. 20), a recent report from Efimova and colleagues identified accelerated senescence in breast cancer xenografts treated with radiation and the PARP inhibitor ABT-888 (42). We similarly found that growth delay of irradiated H460 xenografts by BEZ235 was associated with a robust accelerated senescence response.…”
Section: Discussionsupporting
confidence: 73%
“…While several studies have previously shown that epithelial cancer cells readily undergo senescence after radiation treatment in vitro (reviewed in ref. 20), a recent report from Efimova and colleagues identified accelerated senescence in breast cancer xenografts treated with radiation and the PARP inhibitor ABT-888 (42). We similarly found that growth delay of irradiated H460 xenografts by BEZ235 was associated with a robust accelerated senescence response.…”
Section: Discussionsupporting
confidence: 73%
“…To date, no targeted protocol has been developed for the treatment of triple-negative breast cancer. Although studies show that parp1 (poly[ADP-ribose] polymerase-1) inhibitor can potentially increase the sensitivity of triple-negative breast cancer to radiotherapy 17,18 , treatment of triple-negative breast cancer with parp1 inhibitor and irradiation is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators experimented with altering the patterns of radiotherapy in breast cancer patients with a high risk of lrr, applying targeted biologic therapy 6,[16][17][18] and an increase in the radiation dose. Panoff et al 22 used chest irradiation at the recommended dose of more than 50 Gy and found that the 5-year lrr rate was 5.7% for patients receiving a radiation dose of more than 50.4 Gy (median: 60.4 Gy) and 12.7% for those receiving 50.4 Gy or less (median: 50.4 Gy, p = 0.054).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, radiation is used in a wide range of treatment; over 50% of all cancer treatment protocols include the use of radiation. Target tissues range from skin to skeletal muscles and bone marrow; each tissue type has special cellular components that influence the absorbed radiation dose, and manifests side effects differently.In recent years, cell-based and genetic studies have improved our understanding of the molecular and genetic basis of radiosensitivity by identifying the genes and pathways that are involved in radiation response (Amundson et al 2001(Amundson et al , 2008Smirnov et al 2009;Efimova et al 2010;Niu et al 2010;Noon et al 2010). In this study, we focused on radiation-induced cell death.…”
mentioning
confidence: 99%